Júlio César, de William Shakespeare: Representando Roma e o Ditador, Moldando o Imaginário Popular Inglês - Vieira, Fátima (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Perhaps because it does not contain any complicated scenes of seduction and because it promotes a moral lesson considered important about the characters' reactions to dilemmas that force them to choose between private interest and the common good, Julius Caesar has been one of the most discussed Shakespearean plays in the context of the British school system. The representation of the Roman society that the play offers and, in particular, of Julius Caesar, is one of the most debated issues, and there have been many voices accusing Shakespeare of having distorted the “truth of History”, having transformed Julius Caesar into a tyrant who deserved to die and his killers into true heroes. The play shows, however, a remarkable knowledge of Rome's history by Shakespeare. This paper proposes an analysis of the representation of Rome and Caesar that the play promotes and a reflection on the political message that Shakespeare may have tried to convey to the contemporary audience. Taking into account issues such as the anachronistic elements present in the play and the political and social context of the turn from the 16th to the 17th century, this article describes how, through Julius Caesar, Shakespeare shaped the English popular imagination about Roman times to intervene in pressing political issues of his time.